A single-centre experience of His bundle pacing without electrophysiological mapping system: implant success rate, safety, pacing characteristics and one-year follow up - Swee Leng Kui; Colin Yeo; Lisa Teo; Ai Ling Him; Sherida Binte Syed Hamid; Kelvin Wong; Vern Hsen Tan (Singapore Medical Journal)
Introduction: Despite the challenges related to His bundle pacing (HBP), recent data suggest an improved success rate with experience. As a non-university, non-electrophysiology specialised centre in Singapore, we report our experiences in HBP using pacing system analyser alone. Methods: Data of 28 consecutive patients who underwent HBP from August 2018 to February 2019 was retrospectively obtained. The clinical and technical outcomes of these patients were compared between two timeframes of three months each. Patients were followed up for 12 months. Results: Immediate technical success was achieved in 21 (75.0%) patients (mean age 73.3 ± 10.7 years, 47.6% female). The mean left ventricular ejection fraction was 53.9% ± 12.1%. The indications for HBP were atrioventricular block (n = 13, 61.9%), sinus node dysfunction (n = 7, 33.3%) and upgrade from implantable cardioverter-defibrillator to His-cardiac resynchronisation therapy (n = 1, 4.8%). No significant difference was observed in baseline characteristics between Timeframe 1 and Timeframe 2. Improvements pertaining to mean fluoroscopy time were achieved between the two timeframes. There was one HBP-related complication of lead displacement during Timeframe 1. All patients with successful HBP achieved non-selective His bundle (NSHB) capture, whereas only eight patients had selective His bundle (SHB) capture. NSHB and SHB capture thresholds remained stable at the 12-month follow-up. Conclusion: Permanent HBP is feasible and safe, even without the use of an electrophysiology recording system. This was successfully achieved in 75% of patients, with no adverse clinical outcomes during the follow-up period.